Pengaruh Penerapan Model RADEC Terhadap Kemampuan Berpikir Kreatif Pada Mata Pelajaran IPAS Kelas IV SDN Joglo Surakarta - Karmelia Putri; Hera Heru; Jumanto Jumanto (Departement of Mathematics Education, 2024)
This study aimed to determine the effect of the Read, Answer, Discuss, Explain and Create (RADEC) learning model on creative thinking skills in the Natural and Social Sciences subject of grade IV SDN Joglo in the 2023/2024 academic year. The type of study used is a quantitative approach with an experimental method of one group pre-test post-test design. The population of the study was all students of grade IV SDN Joglo. The sample used in this study was grade IV with a total of 28 students. This study used a saturated sampling technique. Data collection techniques in this study were observation, interviews, tests and documentation. The results of the t-test calculation showed a significant sig value of 0.001 <0.05 and the acquisition of t-count (24.605)> t-count (2.052) at a significance level of α = 0.05. This proves that there is a significant influence between the use of the RADEC model on creative thinking skills in the IPAS subject of grade IV SDN Joglo in the 2023/2024. With the results of this study, it is recommended that elementary school teachers can consider the application of the RADEC learning model as an alternative creative and innovative learning model to improve students' creative thinking skills.